Inkjet‐Printed Flexible Gold Electrode Arrays for Bioelectronic Interfaces. (10th December 2015) - Khan, Yasser; Pavinatto, Felippe J.; Lin, Monica C.; Liao, Amy; Swisher, Sarah L.; Mann, Kaylee; Subramanian, Vivek; Maharbiz, Michel M.; Arias, Ana C.
Abstract : Bioelectronic interfaces require electrodes that are mechanically flexible and chemically inert. Flexibility allows pristine electrode contact to skin and tissue, and chemical inertness prevents electrodes from reacting with biological fluids and living tissues. Therefore, flexible gold electrodes are ideal for bioimpedance and biopotential measurements such as bioimpedance tomography, electrocardiography (ECG), electroencephalography (EEG), and electromyography (EMG). However, a manufacturing process to fabricate gold electrode arrays on plastic substrates is still elusive. In this work, a fabrication and low‐temperature sintering (≈200 °C) technique is demonstrated to fabricate gold electrodes. At low‐temperature sintering conditions, lines of different widths demonstrate different sintering speeds. Therefore, the sintering condition is targeted toward the widest feature in the design layout. Manufactured electrodes show minimum feature size of 62 μm and conductivity values of 5 × 10 6 S m −1 . Utilizing the versatility of printing and plastic electronic processes, electrode arrays consisting of 31 electrodes with electrode‐to‐electrode spacing ranging from 2 to 7 mm are fabricated and used for impedance mapping of conformal surfaces at 15 kHz. Overall, the fabrication process of an inkjet‐printed gold electrode array that is electrically reproducible, mechanically robust, and promising for bioimpedance and biopotential measurements is demonstrated. Abstract : Fabrication of inkjet‐printed flexible gold electrode arrays on plastic substrates is described, with a special focus on laser‐cut freestanding electrodes, low‐temperature sintering, and the methodology used for impedance mapping on conformal surfaces. Taking advantage of low‐cost and large‐area manufacturing techniques, these electrically reproducible and mechanically robust electrode arrays are promising for novel wearable biomedical sensing.